PELATIHAN PENGGUNAAN APLIKASI CANVA DEMI PEMBUATAN KONTEN MARKETING PADA KOMUNITAS PEDAGANG SEPATU CIBADUYUT: Bahasa Indonesia - Saputro, Arie Hendra; Suryaningprang, Andre; Siddiq, Andhika Mochamad; Recky, Recky; Ramdan, Ahmad Taufiq Maulana (Jurnal Abdi Insani, 2024)
The specialty of content marketing is that it can make potential customers who are only interested in finally deciding to make a purchase. The Cibaduyut Shoe Trader Community does not yet recognize and utilize marketing content in business activities. The focus of business activities of the Cibaduyut Shoe trader community is producing shoes and selling shoes conventionally. Conventional business activities include selling to community partners, selling traditionally to sellers or markets. With this activity, it is hoped that you will understand and be able to run and use Canva for content production. Content production is a tool for promoting business or enterprise. This service activity was carried out for 2 months involving students from the University of Indonesia Developing (INABA) and lecturers from the University of Indonesia Developing (INABA). The solution that can be offered is to provide training on using the Canva application to the Cibaduyut Shoe trader community. It is hoped that with training in using the Canva application, partners can create marketing content. The next goal is for the Cibaduyut shoe trader community to be able to market their products not only conventionally but also digitally. Things that partners need to pay attention to are (1) Creating a Canva account; (2) get to know the appearance and use of the Canva application; (3) Create a flyer in the Canva application; (4) Making videos in the Canva application; (5) Using themes and templates; (6) Add sound to flyers or videos; (7) How to download flyers and videos in the Canva application; (8) Change the display format in the Canva application. Partners can follow and understand the training that has been provided. Consistency is the key to being an effective marketing tool.